EVALUASI PENGGUNAAN OBAT PADA PASIEN DISPEPSIA FUNGSIONAL RAWAT JALAN DI RUMAH SAKIT SYARIF HIDAYATULLAH PERIODE JANUARI-DESEMBER 2023 - Nasar, Nur Syariah Afni; Aulia, Gina; Septiyana, Annisa; Fauziah, Vina (PHRASE (Pharmaceutical Science) Journal, 2025)
Health is one of the most important things for survival. Dyspepsia is pain or discomfort in the heartburn, clinical symptoms of dyspepsia in the form of discomfort both persistent (episodic) and recurrent in the upper abdomen. The purpose of this study is to determine the evaluation of drug use in outpatient functional dyspepsia patients at Syarif Hidayatullah Hospital for the January–December 2023 period. The research method in this study is a descriptive research method using a quantitative approach and retrospective data collection. This data collection technique uses Purposive sampling, and 300 samples were obtained in accordance with the research inclusion criteria. The results of the study showed that dyspepsia was mostly experienced by women by 62.7% (188 people), dyspepsia patients were mostly experienced by patients aged 17-26 years by 36.3% (109 people). The type of drug that is most accepted by dyspepsia patients at Syarif Hidayatullah Hospital is sucralfat at 33.5%. The results of the evaluation of the rationality of the use of dyspepsia drugs showed that the diagnosis was 100% accurate, the indication was 100% accurate, the dosage was 100% correct, the drug administration method was 96%, the drug administration time interval was 100%, and the drug administration was 100% long.